Memory as a Commercial Product: The Social Construction of Market Demand for Professional Photography in Moscow - ЕвстратоваАнастасия Павловна (Journal of Economic Sociology, 2013)
The article is devoted to the Moscow market for professional photography, including wedding, portrait, and so called love story pictures. The photographs, which are popular in the market, provide us with an understanding what kind of values can be found in contemporary society and what development trends can be revealed. The author considers photography through the lens of the social senses of photographers and their clients as market actors. The main idea of the paper is to demonstrate how consumer demand for professional photography is socially constructed and what photographers do in order to attract new clients. For that purpose, first the author pays attention to key functions of photography discussed in the existing theoretical literature. Then, she considers the recent studies on self-presentation and image construction within online social networks (also with the help of pictures). Finally, the paper proposes an economic sociological approach to the market for professional photography. This allows the author to deal with the peculiarities of the studied market. In order to find answers through research tasks, the author conducted semi-structured interviews with main market participants, including photographers and their clients (13 interviews). To illustrate consumer preferences, related to image creation, the author presents the results of content analysis of 200 professional pictures posted by users of online social network services. Research findings explain why the preferences and consumers are different and demonstrate a lack of creation and art in the studied market.